Malignant transformation of tailgut cysts is significantly higher than previously reported: systematic review of cases in the literature. (30th April 2019) - Nicoll, K.; Bartrop, C.; Walsh, S.; Foster, R.; Duncan, G.; Payne, C.; Carden, C.
Abstract: Aim: The best treatment for tailgut cysts has not been firmly established. We report a systematic review of the cases in the available literature in order to provide an evidence base for treatment. Method: A systematic search of articles wholly or partly in English was made of PubMed, Embase and Google Scholar; additional studies were discovered by searching reference lists and contacting authors directly. Search terms 'tailgut cyst', 'tail gut cyst', 'retrorectal hamartoma' and 'retrorectal tumour' were used for case reports or case series; no publication date restrictions were imposed. Only studies with histological confirmation of diagnosis and reporting the age and gender of patients were included. Papers were excluded by consensus between the first two authors. Results: A total of 196 individual cases were analysed in detail including 51 cases of neoplasia. The overall rate of neoplastic transformation was 26.6%. Although the male:female cyst incidence ratio was 1:4, men over 18 had a significantly greater relative risk of neoplasm at 1.94 ( P = 0.0055). Radiological evidence of nodular thickening of the cyst wall significantly increased the relative risk of the presence of cancer ( P = 0.0023). Conclusions: Current orthodoxy that these are not dangerous embryological remnants is unfounded and may be false. The available data suggest the risk of malignant transformation is high and will apply to any residual tissue after excision. The same rationale behind total mesorectal excision in rectal cancer applies to tailgut cysts. Consequently they should be resected with similar oncological margins.